Impact of flexible working arrangements (FWAs) on the career productivity of women with domestic duties employed in government agencies - Bautista, Angelica Jan; Chin, Stemarie F.; Lasaca, Bryan Jay S.; Salanap, Necie P.; Dacuyan, Flordeliz B. (Tacloban City Division of Management, University of the Philippines Tacloban College, 2025)
This study investigated the impact of Flexible Working Arrangements (FWAs) on the career productivity of women with domestic duties employed in government agencies in Tacloban City. Through a convergent mixed-methods design, the research combined qualitative analysis of FWA policy memorandums from five government agencies using thematic analysis and gathered survey responses from 58 women employees for the quantitative analysis. The qualitative findings identified five key themes of FWAs policies: (1) Administrative Compliance, (2) Disaster Response and Mitigation, (3) Health and Well-being. (4) Agency Productivity, and (5) Employee-Specific Considerations. These themes function as guiding principles in the formulation and implementation of FWA policies, revealing that while bureaucratic imperatives are prioritized, disaster response, mitigation, health, and well-being are the driving force for FWAs to be formulated. This suggests that when these factors are incorporated, higher productivity is achieved by integrating employee-specific considerations. Quantitative analysis demonstrated that FWAs significantly boost career productivity, primarily through increased job satisfaction and output turnover, whilst effect on stress reduction was statistically insignificant. Output turnover exhibited a strong positive correlation with overall productivity ( r = 0.703 p < 0.001 ) while job satisfaction showed an even stronger positive correlation ( r = 0.806 , p < 0.001 ) indicating that employees who experience higher satisfaction and output levels are more productive. Conversely, stress showed a negative but non-significant correlation with productivity ( r = - 0.107 , p = 0.425 ), Overall, the integration of the five thematic considerations contributes positively to employee outcomes, highlighting the importance in enhancing career productivity through output turnover and job satisfaction among women managing both career and domestic duties.
Undergraduate thesis (Bachelor of Science in Accountancy) -- University of the Philippines, Tacloban.
Keywords: Public employees -- Flexible work arrangements -- Tacloban City; Flexible working arrangements (FWAs).; Career productivity; Women employees; Domestic duties; Government agencies